Diagnostic performance of a urine-based ELISA assay for the screening of human schistosomiasis japonica: A comparative study - Mu, Yi; Weerakoon, Kosala G.; Olveda, Remigio M.; Ross, Allen G.; McManus, Donald P.; Cai, Pengfei (Frontiers in Microbiology, 2022)
The current study developed and evaluated the performance of a urine-based enzyme-linked immunosorbent assay (ELISA) for the screening of S. japonicum infection in a human cohort (n = 412) recruited from endemic areas, Northern Samar, the Philippines. The diagnostic performance of the urine ELISA assay was further compared with the Kato-Katz (KK) technique, serum-based ELISA assays, point-of-care circulating cathodic antigen (POC-CCA) urine cassette test and droplet digital (dd)PCR assays performed on faeces, serum, urine and saliva samples, which were designated as F_ddPCR, SR_ddPCR, U_ddPCR and SL_ddPCR, respectively. When urine samples concentrated 16× were assessed, the SjSAP4 + Sj23-LHD-ELISA (U) showed sensitivity/specificity values of 47.2/93.8% for the detection of S. japonicum infection in KK-positive individuals (n=108). The prevalence of S. japonicum infection in the total cohort (n = 412) determined by the urine ELISA assay was 48.8%, which was lower than that of F_ddPCR (74.5%, p < 0.001), SR_ddPCR (67.2%, p < 0.001), and SjSAP4 + Sj23-LHD-ELISA (S) (66.0%, p < 0.001), but higher than that determined by the Sj23-LHD-ELISA (S) (24.5%, p < 0.001), POC-CCA assay (12.4%, p < 0.001) and SL_ddPCR (25.5%, p < 0.001), with a diagnostic level of performance similar to that obtained with the urine ddPCR (47.6%, p > 0.05). Using the other diagnostic tests as a reference, the urine ELISA assay showed a sensitivity between 47.2-56.9%, a specificity between 50.7-55.2% and an accuracy between 49.3-53.4%. The concentrated-urine SjSAP4 + Sj23-LHD-ELISA developed in the current study was more sensitive than both the KK test and POC-CCA assay, and showed a comparable level of diagnostic accuracy to that of the U_ddPCR. However, its diagnostic performance was less robust than the F_ddPCR, SR_ddPCR, and SjSAP4 + Sj23-LHD-ELISA (S) assays. Although they are convenient and involve a highly acceptable non-invasive procedure for clinical sample collection, the insufficient sensitivity of the three urine-based assays (urine ELISA, U_ddPCR assay and the POC-CCA assay) will limit their value for the routine screening of schistosomiasis japonica in the post mass drug administration (MDA) era, where low-intensity infections are predominant in many endemic areas.